The effect of deprivation on coronary heart disease mortality rate. (1st September 2018) - Theocharidou, Lambrini; Mulvey, Matt R
Abstract: Deprivation and socioeconomic status are associated with cardiovascular diseases. The aim of this study is to describe a relationship between socioeconomic deprivation and coronary heart disease (CHD) mortality. This study used publicly available data for English Indices of Multiple Deprivation (IMD) and CHD mortality rate. IMD data is a ranked score based on seven factors related to socioeconomic status. The average IMD rank and the average CHD mortality rate were collected from the Office of National Statistics website for each Clinical Commissioning Group (CCG) in UK. To investigate the relationship between IMD score and CHD mortality a linear regression was fitted using logged CHD data, because the spread of the CHD data was largest for higher values of IMD. This achieved a more symmetrical distribution of the data. The results from the regression model were retransformed to values representing the original CHD data. Analysis was performed using data from 209 CCGs. CHD mortality rate for the lowest IMD ranked CCG is 27.6 and for the highest 97.4. Using the log-CHD values, the linear regression model revealed that for a one-point increase in IMD rank score, CHD mortality rate increases by 1.03 on average (95% CI 1.02–1.03; P < 0.001). These data show that areas with higher deprivation had higher rates of mortality from CHD. These findings are supported by previous research, which emphasize the important relationship between socioeconomic status and public health crises.